2008
DOI: 10.1007/s00114-007-0335-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronodisruption and cancer

Abstract: Research into health effects of chronodisruption (CD), a relevant disturbance of the circadian organization of physiology, endocrinology, metabolism and behaviour, is evolving at a rapid pace. With regard to malignancies, our synthesis of key experiments indicates that CD can play a causal role for cancer growth and tumor progression in animals. Moreover, our meta-analyses of 30 epidemiological studies evince that flight personnel and shift workers exposed to chronodisruption may have increased breast and pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 80 publications
2
83
0
4
Order By: Relevance
“…www-dep.iarc.fr/globocan/database.htm, 8,9,10). Empirically, recent meta-analyses evinced that-in line with predictions following from the chronodisruption hypothesis or theory-not only breast cancer [the summary relative risks for investigations of flight personnel and shift workers suggested a respective 70% and 40% increase, respectively, in the risk (6)], but also prostate cancer risks appear to be significantly increased [summary relative risks for investigations of flight personnel conveyed a 40% increase in the risk (6)], likely exposed to chronodisruption via transmeridian, time-zone travel and shiftwork conditions. On the other hand, a large cohort study of cancer risk in Sweden, published only in October of 2007 and thus not included in these metaanalyses, found no evidence for an association between shift work and breast or prostate cancer (11).…”
Section: A Dilemma Of Shift Work and Chronodisruption Researchmentioning
confidence: 88%
“…www-dep.iarc.fr/globocan/database.htm, 8,9,10). Empirically, recent meta-analyses evinced that-in line with predictions following from the chronodisruption hypothesis or theory-not only breast cancer [the summary relative risks for investigations of flight personnel and shift workers suggested a respective 70% and 40% increase, respectively, in the risk (6)], but also prostate cancer risks appear to be significantly increased [summary relative risks for investigations of flight personnel conveyed a 40% increase in the risk (6)], likely exposed to chronodisruption via transmeridian, time-zone travel and shiftwork conditions. On the other hand, a large cohort study of cancer risk in Sweden, published only in October of 2007 and thus not included in these metaanalyses, found no evidence for an association between shift work and breast or prostate cancer (11).…”
Section: A Dilemma Of Shift Work and Chronodisruption Researchmentioning
confidence: 88%
“…MLT suppression by ALAN has a dose-dependent response to both irradiance level and duration of the exposure [223]. Furthermore, the phase advance and suppression in MLT rhythms are intimately wavelength-dependent with more manifested effect at short wavelengths compared with long wavelengths [44,45,224]. Finally, the ALAN-induced MLT suppression is not age-related [225].…”
Section: Circadian Disruption Biomarkers In Obesity and Cancer Researchmentioning
confidence: 98%
“…Accordingly, a comprehensive study on the effect of various artificial lights on MLT suppression revealed that 4000 K and 5000 K LED lights were the most effective in the suppression of the hormone compared with counterpart technologies, such as incandescent, halogen, and florescent lightening systems [46]. Furthermore, a different study demonstrated an inverse association between MLT synthesis and the irradiances of narrowband blue LED exposure (peak λ = 469 nm; ½ peak bandwidth = 26 nm), and the impact of this spectrum was evidently larger than that of 4000 K of white florescent at twice the energy of the former [44,47]. Finally, the negative effects of circadian disruption on public health are expected to be exacerbated by the increasing exposure to ALAN of LED illumination emitted from variant sources, including electronic screens used by people of all ages, particularly adolescents [48].…”
Section: Circadian Disruptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, though, as long as causality is not established, we should clearly be deterred from activities that are not driven by data. Moreover, means for primary prevention are elusive (Erren et al 2009): Shift-work is unavoidable in our 24/7 societies, and it is impossible with today’s state of knowledge to identify workers who are robust to shift-work conditions and to dissuade others who may be susceptible to the effects of circadian disruption or chronodisruption (Erren et al 2008; Erren and Reiter 2008). An IARC classification of “probable” human carcinogen, which implies uncertainty and the possibility that future research may exonerate the “culprit in question,” is certainly not an appropriate yardstick to guide valuable and limited resources.…”
mentioning
confidence: 99%